Maternal Immunoglobulins in Infants—Are They More Than Just a Form of Passive Immunity? - Pierzynowska, Kateryna; Woliński, Jarosław; Weström, Björn; Pierzynowski, Stefan G. (Frontiers in Immunology, 2020)
In the present review we highlight the possible ‘extra-immunological’ effects of maternal immunoglobulins (Ig) transferred to the blood circulation of offspring, either via the placenta before birth or via the colostrum/milk across the gut after birth in different mammalian species. Using the newborn pig as a model, since they are naturally born agammaglobulinemic intravenously (i.v.) infused purified serum Ig rapidly improved the vitality, suckling behaviour and ensured the survival of both preterm and term piglets. In further studies we found that proper brain development requires i.v. Ig supplementation. Studies have reported positive effects of i.v. Ig treatment in children with epilepsy. Moreover, feeding newborn pigs an elementary diet supplemented with Ig improved the gut structure, and recently a positive impact of enteral or parenteral Ig supplementation on the absorption of polyunsaturated fatty acids (PUFAs) was observed in the newborn pig. Summarized, our own results and those found in the literature, indicate the existence of important extra-immune effects of maternal Ig, in addition to the classical protective effects of transferred maternal passive immunity, including effects on the development of the brain, gut and possibly other organ systems in the neonate. These additional properties of circulating Ig could have an impact on care guidelines for human neonates, especially those born prematurely with low plasma Ig levels.